Human activities can hinder the breeding of a top avian predator: preliminary results - Dobromir D. Dobrev; Vladimir D. Dobrev; Dimitar A. Demerdzhiev (Пернатые хищники и их охрана)
The Eastern Imperial Eagle (Aquila heliaca, EIE) is a large-sized, globally threatened species with a wide distribution. The species is extremely vulnerable and sensitive to human disturbance and activities in the vicinity of its nests. We analyzed the effect of human disturbance on two territories of Eastern Imperial Eagles from Bulgaria in 2008–2009.